Use of locoregional Perforator Flaps for reconstruction of lower limb defects: Our experience (Indian Journal of Applied-Basic Medical Sciences, 2021)
BACKGROUND: Popularity of perforator flaps for lower limb reconstruction has increased due to multiple  advantages. It gives replacement of tissues using ‘like-by-like’ principles.  METHODS: From December 2018 to January 2020, 11 cases of lower limb reconstruction were operated using  perforator flaps. Outcome was assessed in view of age distribution, duration of surgery, hospital stay,  postoperative complications, patient satisfaction & cosmesis. RESULTS: Partial flap necrosis was noted as most common (three cases) postoperative complication in our study.  Other complications were superficial epidermolysis, venous congestion & total flap loss which were managed  conservatively except one case in which skin grafting was performed after debridement of totally necrosed flap. CONCLUSIONS: Perforator flaps are having relatively simple surgical technique & advantage of less donor site  morbidity. Identification of various perforators in lower limb makes its use more feasible for lower limb  reconstruction.
Keywords: Perforator flaps; Lower limb reconstruction